Content Analysis of Editorials in Bhirawa Newspaper: Analisis Isi Tajuk Rencana Pada Surat Kabar Bhirawa - Rijal, Moch. Choirul; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to describe the content analysis of editorials in the bhirwa newspaper (a descriptive study of the content analysis of editorials in the bhirawa newspaper about political news in the month of October 2019). This research uses content analysis theory which focuses on pragmatic and semantic analysis. The research method used is qualitative content analysis. The research data was obtained by documenting every political news in the daily editorial of Bhirawa. The results of this study stated that the editorial on the daily political news of Bhirawa in the period of October 2019 mostly highlighted the failure of government agencies, except for the Indonesian National Army or TNI agencies which were reported to have a populist attitude. This indicates that in the 2019 presidential election, Bhirawa daily supported one candidate with a military background. Semantically, the reporting carried out by Bhirawa can be interpreted that the incumbent presidential candidate still has many problems in his leadership, except for the TNI. This can be interpreted that the neutrality of newspapers in overseeing government policy issues is not completely neutral